If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 + 2(3 + x) = 0 3x + 7 + (3 * 2 + x * 2) = 0 3x + 7 + (6 + 2x) = 0 Reorder the terms: 7 + 6 + 3x + 2x = 0 Combine like terms: 7 + 6 = 13 13 + 3x + 2x = 0 Combine like terms: 3x + 2x = 5x 13 + 5x = 0 Solving 13 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 5x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 5x = 0 + -13 5x = 0 + -13 Combine like terms: 0 + -13 = -13 5x = -13 Divide each side by '5'. x = -2.6 Simplifying x = -2.6
| 4x+10=2+6x | | 24+7x=12+10x | | 2x+30=10+7 | | 42+4x=10x+24 | | 3x+7+3(3+x)= | | 20+15x=70+5x | | 66+12x=1x+88 | | 6x+64=14x+48 | | 7x+40=10+12x | | (5/6x)-2x=(5/3)-(8/3) | | 33+14x=55+3x | | 8+3x=4+7x | | 32+13x=5x+48 | | 66+2x=13x+55 | | 18+11x=5x+30 | | 14x+24=2x+72 | | 3x+50=13x+30 | | 42+8x=14x+12 | | 20+14x=30+4x | | 2x+12=6+8x | | 6+8x=15+5x | | 6+5x=4+6x | | 6x+9=7x+6 | | 12+8x=12x+8 | | 8+7x=16+3x | | 7+14x=7x+35 | | 28+11x=4x+56 | | 7+14y=7x+35 | | 21+4x=9+7x | | 84+2x=24+14x | | 15+12x=18+9x | | 18+11x=2x+45 |